Seasonal climatic niche-switching migration in the Nearctic-Neotropical Rufous Hummingbird (Selasphorus rufus) - Edson A. Alvarez-Alvarez; R. Carlos Almazán-Núñez; Felipe A. Toro-Cardona; L. Gerardo Herrera M; María José Tolsá-García; Oscar Talavera-Mendoza; Martha Lopezaraiza-Mikel (PLoS ONE, 2025)
Migratory birds inhabit diverse geographic regions during their reproductive and wintering periods; however, information regarding the climatic conditions that enable migratory birds, particularly hummingbirds, to thrive in these regions is limited. This study aimed to characterize the geographic distribution and seasonal climatic niche of the Nearctic–Neotropical Rufous Hummingbird ( Selasphorus rufus )—classified as near threatened—across its reproductive and wintering areas in North America. We obtained monthly occurrence records for the Rufous Hummingbird during its reproductive (May to June) and wintering (November to January) periods. We generated seasonal ecological niche models to reconstruct the climatic space occupied by the Rufous Hummingbird during these periods and evaluated climatic differences through niche similarity analysis. Our results indicate that the Rufous Hummingbird is a longitudinally migratory species that engages in niche-switching, occupying distinct climatic conditions in its reproductive and wintering areas across Mexico and the eastern United States. Changes in the climatic niche of the Rufous Hummingbird may be linked to its adaptive plasticity in response to varying climatic conditions, competition for resources, and recent climate change. These findings have biogeographic, evolutionary, and conservation implications for the Rufous Hummingbird and other migratory birds with similar movement patterns.